2020
DOI: 10.3390/ijms21176174
|View full text |Cite
|
Sign up to set email alerts
|

“Clicking” an Ionic Liquid to a Potent Antimicrobial Peptide: On the Route towards Improved Stability

Abstract: A covalent conjugate between an antibacterial ionic liquid and an antimicrobial peptide was produced via “click” chemistry, and found to retain the parent peptide’s activity against multidrug-resistant clinical isolates of Gram-negative bacteria, and antibiofilm action on a resistant clinical isolate of Klebsiella pneumoniae, while exhibiting much improved stability towards tyrosinase-mediated modifications. This unprecedented communication is a prelude for the promise held by ionic liquids -based approaches a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…For instance, the 1-alkyl-3-methyl imidazolium IL has been conjugated with silver and copper-containing anions to improve the antimicrobial activity against a range of pathogenic bacteria and fungi [ 170 ]. In another approach, an antibacterial ionic liquid and an antimicrobial peptide were conjugated via “click” chemistry, generating antimicrobial activity against Gram-negative multidrug-resistant clinical isolates, and antibiofilm action towards a resistant clinical Klebsiella pneumoniae isolate [ 184 ]. The introduction of organic salts from ciprofloxacin and norfloxacin as anions has been recently proven to enhance the antimicrobial activity against K. pneumoniae S. aureus and Bacillus subtilis strains [ 185 ].…”
Section: Biomedical Applications Of Ionic Liquids-based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the 1-alkyl-3-methyl imidazolium IL has been conjugated with silver and copper-containing anions to improve the antimicrobial activity against a range of pathogenic bacteria and fungi [ 170 ]. In another approach, an antibacterial ionic liquid and an antimicrobial peptide were conjugated via “click” chemistry, generating antimicrobial activity against Gram-negative multidrug-resistant clinical isolates, and antibiofilm action towards a resistant clinical Klebsiella pneumoniae isolate [ 184 ]. The introduction of organic salts from ciprofloxacin and norfloxacin as anions has been recently proven to enhance the antimicrobial activity against K. pneumoniae S. aureus and Bacillus subtilis strains [ 185 ].…”
Section: Biomedical Applications Of Ionic Liquids-based Materialsmentioning
confidence: 99%
“…A covalent conjugate between an antibacterial IL and an antimicrobial peptide was produced via “click” chemistry. The resulting compound was found to maintain the peptide’s antimicrobial activity against Gram-negative bacteria multidrug-resistant clinical isolates as well as improved stability towards tyrosinase-mediated modifications [ 184 ].…”
Section: Biomedical Applications Of Ionic Liquids-based Materialsmentioning
confidence: 99%
“…This study confirmed the potent synergic action against both E. coli and S. aureus when the HDP is combined with the ILs, and revealed a correlation between antimicrobial potency, which improved with the increase of the alkyl chain length in the IL [ 172 ]. Another example is the work reported by Gomes and co-workers [ 173 ]. In this study, coupling an antimicrobial methylimidazolium IL to the N -terminus of a collagenesis-inducing peptide with potent antibacterial and antibiofilm properties, delivered a covalent conjugate that retained the parent peptide’s activity against multidrug-resistant clinical isolates of Gram-negative bacteria, and antibiofilm action on a resistant clinical isolate of Klebsiella pneumoniae , while exhibiting much improved stability towards tyrosinase-mediated modifications [ 173 ].…”
Section: Ionic Liquid-based Approaches In Dermal and Transdermal Drug Deliverymentioning
confidence: 99%
“…Another example is the work reported by Gomes and co-workers [ 173 ]. In this study, coupling an antimicrobial methylimidazolium IL to the N -terminus of a collagenesis-inducing peptide with potent antibacterial and antibiofilm properties, delivered a covalent conjugate that retained the parent peptide’s activity against multidrug-resistant clinical isolates of Gram-negative bacteria, and antibiofilm action on a resistant clinical isolate of Klebsiella pneumoniae , while exhibiting much improved stability towards tyrosinase-mediated modifications [ 173 ]. These above-mentioned works are an overture for the potential held by IL-based strategies as tools to improve the properties of bioactive peptides.…”
Section: Ionic Liquid-based Approaches In Dermal and Transdermal Drug Deliverymentioning
confidence: 99%
“…With the above in mind, we previously reported a set of hybrid constructs where a collagen boosting peptide (CBP), the well-known "pentapeptide-4" (PP4), was covalently linked to an antimicrobial peptide (AMP), 3.1, using different orientations, spacers, and N-terminal modifications, aiming at a dual-action peptide with therapeutic potential to tackle cSSTI [13,14]. This study revealed that the peptide 3.1-PP4 has potent and selective activity against Gram-negative bacteria, including MDR clinical isolates, both in planktonic and biofilm forms [13].…”
Section: Introductionmentioning
confidence: 99%